2021
DOI: 10.3389/fmolb.2021.625858
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Molecular Subtypes of Hepatocellular Carcinoma Based on Dysregulated Immune LncRNAs

Abstract: Long non-coding RNAs (lncRNAs) as important regulators of gene expression also have critical functions in immune regulation. This study identified lncRNA modulators of immune-related pathways as biomarkers for hepatocellular carcinoma (HCC). The profile of lncRNA regulation in immune pathways in HCC was comprehensively mapped. To determine lncRNAs with immunomodulatory functions specific to HCC, the enrichment of lncRNAs in a collection of 17 immune functions was calculated applying gene set enrichment analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been reported that MCCC1-AS1 may be related to the prognosis of endometrial carcinoma of the uterine corpus [49]. LINC02416 is highly expressed in hepatocellular carcinoma [50]. The underlying mechanisms by which these lncRNAs exert their effects deserve further study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MCCC1-AS1 may be related to the prognosis of endometrial carcinoma of the uterine corpus [49]. LINC02416 is highly expressed in hepatocellular carcinoma [50]. The underlying mechanisms by which these lncRNAs exert their effects deserve further study.…”
Section: Discussionmentioning
confidence: 99%